Preparation and Characterization of CaMoO4 by Solid-State Microwave Metathetic Route - Sung Lim, Chang (Asian Journal of Chemistry, 2011)
A solid-state metathetic (SSM) route assisted by microwave irradiation was used to synthesize the CaMoO4 particles in 10 min under environmentally friendly conditions. Well crystallized CaMoO4 particles were formed at 600 ºC for 3 h, showing a fine and homogeneous morphology with sizes of 1-3 μm. The synthesized CaMoO4 particles were characterized by X-ray diffraction, Fourier transform infrared spectroscopy and scanning electron microscopy. The optical properties were examined by photoluminescence emission and Raman spectroscopy.